Thermoresponsive self-assembled cyclodextrin-end-decorated PNIPAM for aqueous catalysis1. Issue 12 (11th February 2015) - Potier, J.; Menuel, S.; Lyskawa, J.; Fournier, D.; Stoffelbach, F.; Monflier, E.; Woisel, P.; Hapiot, F.
<x xml:space="preserve">Abstract</x> The catalytic performance of thermoresponsive poly(N-isopropylacrylamide) (PNIPAM) functionalized at the terminal position with randomly methylated β-cyclodextrin was demonstrated by the aqueous Rh-catalysed hydroformylation of higher olefins.